درجة اكتساب المهارات المهنية اللازمة لسوق العمل لدى الطالبات المتوقع تخرجهن من كلية المجتمع بالحناكية - جامعة طيبة - الرحيلي، مريم أحمد فايز; السيد، إلهام محمود; صبر، صفيات علي; الأحمدي، وداد (جامعة طيبة - كلية التربية, 2019)
هدفت هذه الدراسة إلى التعرف إلى درجة اكتساب المهارات المهنية المطلوبة لسوق العمل لدى طالبات برنامجين من برامج كلية المجتمع بالحناكية، هما: الشبكات، وبرمجة الحاسب، وتحديد معنوية الفروق بين الطالبات في البرنامجين من حيث متوسط درجة اكتسابهن لتلك المهارات، وكذلك التعرف إلى آراء الطالبات في إيجابيات البرنامجين وسلبياتهما ومقترحات التطوير. وقد توصلت الدراسة إلى أن متوسط درجة اكتساب الطالبات للمهارات المهنية المطلوبة لسوق العمل في البرنامجين مرتفعة. كما تبين عدم وجود فروق بين طالبات البرنامجين في درجة اكتسابهن لتلك المهارات. كذلك تبين أن أكثر المهارات الإيجابية التي ذكرتها الطالبات في برنامج الشبكات هي: اكتساب مهارات الحاسب الآلي وتطبيقاته، ومهارات عمل شبكة محلية والريط بين الشبكات، ومهارات سرية المعلومات وأمنها. أما أكثر هذه الإيجابيات في برنامج برمجة الحاسب ونظم المعلومات فكانت: اكتساب مهارات الحاسب الآلي وتطبيقاته، وتعلم كيفية البرمجة وإنشاء صفحات الويب والرسوم والألعاب، وتطبيقات الهواتف الذكية. وقد اتفقت الطالبات في البرنامجين على أن أكثر السلبيات قد تركزت حول ما يلي: ضعف صيانة الأجهزة والبرامج في المعامل، وعدم كفاية الوقت المخصص للتطبيقات العملية. وتلخصت مقترحاتهن في المطالب الأربعة التالية: زيادة ساعات التطبيق العملي، وتنظيم دورات تدريبية داخل الكلية لزيادة اكتساب المهارات، وإنشاء نظام للصيانة وتحديث الأجهزة في المعامل، وإدخال الأجهزة اللوحية الحديثة إلى المعامل. وبناء على هذه النتائج، أوصت الدراسة بتدعيم المهارات المكسبة باعتبارها مهارات تميز لخريجات الكلية، مع وضع خطط تحسين للمهارات التي جاءت درجة الاكتساب فيها ضعيفة، وعلاج الجوانب السلبية، والعمل بمقترحات الطالبات للتحسين، وإجراء هذه الدراسة بشكل سنوي لمتابعة تنفيذ خطط التحسين، والتعرف إلى الآثار الناشئة عنها، وتطوير هذه الدراسة لتشمل فئات أخرى، منها آراء أرباب العمل في مهارات الخريجات وحالة التوظيف بعد سنة من التخرج.
The aim of this study is to identify the degree of acquisition of the professional skills required for the labor market by students of computer networks and computer programming and information systems, as well as to determine the significance of the differences between the students in the two programs in terms of the average degree of their acquisition of these skills, in addition to the students' opinions on the pros and cons of the programs’ development. The study found that the average degree of female students acquiring the professional skills required for the labor market in both programs is high. There were no differences between the students of the two programs in the degree to which they acquired these skills. The most positive skills mentioned by students in the networking program were: acquisition of computer skills and applications, local networking skills and networking and confidentiality and information security skills. The most common of these advantages in the program of computer programming and information systems were: acquisition of computer skills and applications, learning how to program and create web pages, graphics and games and smart phone applications. In both programs, the students agreed upon that the most negative aspects were: poor maintenance of hardware and software in laboratories and insufficient time for practical applications. Their proposals can be summarized in the following four demands: increasing the hours of practical application, organizing training courses within the college to increase the acquisition of skills, establishing a system of maintenance and modernization of devices in laboratories and introducing modern tablet devices in laboratories. Based on these results, the study recommended strengthening the acquired skills as distinct skills for the college graduates, developing improvement plans for the skills that resulted in weak grades, treating the negative aspects and working on the students' suggestions for improvement. This study should be conducted annually to follow up the implementation of the improvement plans and to develop this study to include other categories, including the views of employers regarding the skills of graduates and the status of employment after one year of graduation.
Keywords: طلبة الجامعة -- البرامج الدراسية -- المهارات المهنية -- سوق العمل -- كلية المجتمع بالحناكية -- جامعة طيبة